Hyperthermic intraperitoneal chemotherapy after secondary cytoreduction in epithelial ovarian cancer: A single-center experience - Naki, Mehmet Murat; Aykanat, Yeliz; Alkhan, Fatema; Sağır Gökdağlı, Fulya; Köse, Mehmet Faruk (Lippincott Williams, 2016)
[Abstract Not Available]
Keywords: Hyperthermic; Intraperitoneal Chemotherapy; Ovarian Cancer